2022
DOI: 10.1126/sciadv.abq4617
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant treatment of PDX models reveals patterns of neuroblastoma chemoresistance

Abstract: Chemotherapy resistance and relapses are common in high-risk neuroblastoma (NB). Here, we developed a clinically relevant in vivo treatment protocol mimicking the first-line five-chemotherapy treatment regimen of high-risk NB and applied this protocol to mice with MYCN -amplified NB patient-derived xenografts (PDXs). Genomic and transcriptomic analyses were used to reveal NB chemoresistance mechanisms. Intrinsic resistance was associated with high genetic diversity and an embryonic phen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 70 publications
2
18
0
Order By: Relevance
“…However, serial in vivo passaging of orthotopic NB PDXs for up to two years has shown that PDXs retain key genetic aberrations (e.g., 1p loss, MYCN amplification, and 17q gain) and acquire only minor genetic changes over time, as would be expected from their natural evolution ( 39 ). Clonal dynamics studies during tumor progression in PDXs have shown the presence of branched evolution, clonal sweeps, and convergent evolution of specific small deletions in potentially tumor-associated genes ( 46 ), a pattern similar to tumor evolution in NB patients ( 47 ).…”
Section: Pd Nb Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, serial in vivo passaging of orthotopic NB PDXs for up to two years has shown that PDXs retain key genetic aberrations (e.g., 1p loss, MYCN amplification, and 17q gain) and acquire only minor genetic changes over time, as would be expected from their natural evolution ( 39 ). Clonal dynamics studies during tumor progression in PDXs have shown the presence of branched evolution, clonal sweeps, and convergent evolution of specific small deletions in potentially tumor-associated genes ( 46 ), a pattern similar to tumor evolution in NB patients ( 47 ).…”
Section: Pd Nb Modelsmentioning
confidence: 99%
“…A few studies have used PD models to identify diverse mechanisms implicated in NB invasion, migration, metastasis ( 64 , 65 ), and resistance to specific chemotherapies ( 66 ). Using a clinically relevant treatment protocol (COJEC-induction therapy), NB PDXs show similar chemotherapy responses to their corresponding patients, suggesting that NB PDXs are useful for modelling chemoresistance and relapse ( 46 ). The models showed that chemoresistant NBs have a lower ADR signature and enrichment for an immature MES-like phenotype, suggesting an association between the MES cell state and relapse ( 46 ).…”
Section: Applications Of Pd Nb Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…PDXs avoid cell selection and adaptation typical of in vitro conditions, hence allowing a more comprehensive representation of the diversity of high-risk neuroblastomas. Moreover, this model provides opportunities to refine personalized therapy recommendations for neuroblastoma patients [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%